Arginine methylation of HSPA8 by PRMT9 inhibits ferroptosis to accelerate hepatitis B virus-associated hepatocellular carcinoma progression - Deng, Wensheng; Ai, Jiaoyu; Zhang, Wanlin; Zhou, Zhenyu; Li, Muqi; Yan, Likun; Zhang, Lidong; Huang, Zongjing; Wu, Ziyi; Ai, Junhua; Jiang, Hai (Journal of translational medicine, 2023)
Background The hepatitis B virus X (HBx) protein is an established cause of hepatitis B virus (HBV)-induced hepatocellular carcinoma (HCC). Whether arginine methylation regulates ferroptosis involved in HBx-induced HCC progression has not been reported. This study aimed to explore whether HBx-regulated protein arginine methyltransferase 9 (PRMT9) mediates the involvement of ferroptosis in the development of HCC. Methods and results HBx inhibited ferroptosis through promoting PRMT9 expression in HCC cells. PRMT9 suppressed ferroptosis to accelerate HCC progression in vivo. PRMT9 targeted HSPA8 and enhanced arginine methylation of HSPA8 at R76 and R100 to regulate ferroptosis in HCC. HSPA8 overexpression altered the transcriptome profile of HepG2 cells, in particular, ferroptosis and immune-related pathways were significantly enriched by differentially expressed genes, including CD44. HSPA8 overexpression up-regulated CD44 expression and knockdown of CD44 significantly reversed the inhibition of ferroptosis caused by PRMT9 overexpression. Conclusions In conclusion, HBx/PRMT9/HSPA8/CD44 axis is a vital signal pathway regulating ferroptosis in HCC cells. This study provides new opportunities and targets for the treatment of HBV-induced HCC. Graphical Keywords: Hepatitis B virus X, Hepatocellular carcinoma, Ferroptosis, Arginine methylation, PRMT9, HSPA8, CD44